Management of radiology services during the 2022 FIFA football (soccer) World Cup - Marcelo Bordalo (17704395) (2023)
Diagnostic imaging is the predominant medical service sought for the assessment and staging of musculoskeletal injuries in professional sports events. During the 2022 FIFA Football (soccer) World Cup, a centralized medical care infrastructure was established. This article provides a comprehensive account of the radiological services implemented during this event, encompassing the deployment of equipment and human resources, the structuring of workflows to uphold athlete confidentiality, and initiatives aimed at enhancing communication. Communication channels were refined through radiology consultations held with national teams’ health care providers and the adoption of audiovisual reports available in multiple languages, which could be accessed remotely by team physicians. Our established framework can be replicated in international professional football events for seamless integration and efficacy. Other Information Published in: Skeletal Radiology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00256-023-04486-2